IMPLEMENTASI KEBIJAKAN PENGEMBANGAN SISTEM JARINGAN IRIGASI DI DESA SULI INDAH KECAMATAN BALINGGI KABUPATEN PARIGI MOUTONG - Reza, Fachrul (Katalogis, 2016)
The purpose of this study was to determine the Development Policy Implementation Irrigation Systems in Suli Indah subdistrict Balinggi Moutong Parigi district, in this case the Technical Implementation Unit of the Department of Agriculture and Animal Husbandry Kecamtan Balinggi. The theory that is in use is the theory of Edward III, the factors being addressed: Communication, Resources, Disposition, Bureaucratic Structure. With qualitative research methods. Informants in this study is the Head of the Executive Unit Technical Department of Agriculture and Peternakn District of Balinggi, Head of Agricultural Extension District of Balinggi, Agricultural Extension Workers, fostering farmer in the village of Suli Indah, 2 People Farmers in Suli Indah, Chairman of the Water User Farmers Suli Indah , Community Leaders In Suli Indah targeted research. Data collection techniques used are obserfasi, interviews and documentation. The results showed that the implementation of development policies Irrigation Systems In Suli Indah subdistrict Balinggi Moutong Parigi district has been running well, however they must be repaired communication because not maximized. In view of the factors Resources, Disposition, Bureaucratic Structure, communication factor in view less because there are still farmers who do not know about this program does not come in because many times in meetings, and dissemination of which is held by the sub-district agricultural office Balinggi.